Assessment of Psychosocial Outcomes for Patients Who Had Undergone Cardiac Surgery in Baghdad City - Sundus ali, (Iraqi National Journal of Nursing Specialties, 2023)
Objective: The study aimed to assess the psychological outcomes for patients who were undergone cardiacsurgery (CABG and VR) and to find a relationship between the psychosocial outcomes.Methodology: A descriptive-analytic study was conducted on (50) patient was selected purposively and whot¥:i;u,#r§i#a:rsfi¥r8i%atan£[sheafe:)f°+'h°ews-:£yc*n:Cc°£L?d°o:dd;:len;u::]Cpae]r]::S::i:gn4A:-Z6#A questiormaire was adopted and developed that consists of two parts, the first was related to demographiccharacteristics of the sample, and the second was concerned with psychosocial outcomes, and it consists of 48item that describe the psychological outcomes (anxiety, depression and anger) and the social outcomes.Data were analysed through the use of the suitable statistical methods.Results: The results of the study revealed that patients suffer from severe level of psychological outcomes(anxiety, depression and anger) and from moderate level of social outcomes.Recommendations: The study recommended establishing a cardiac rehabilhation and counselor units to help inreducing psychological risk factors for patients who were undergone cardiac surgery to improve the quality oflife and establishing an educational program for the nurses and the patients' families concerning the psychosocialand social complications for these patients.